Hubungan Pengetahuan, Motivasi dan Dukungan Rumah Sakit terhadap Penrapan Keselamatan Kesehatan Kerja Perawat - Sri Rahayu; Innama Sakinah; Irmansyah (Faletehan Health Journal, 2025)
Occupational Health and Safety (OHS) is a crucial aspect in the hospital environment to protect health workers from various occupational risks. The implementation of hospital OHS not only aims to prevent occupational accidents and occupational diseases but also creates a safe and comfortable hospital environment for patients, all employees, and visitors. This study aims to analyze the relationship between knowledge, motivation, and hospital support to the implementation of hospital OHS. This study used a descriptive method with a cross-sectional approach. The research instrument was a closed questionnaire. The research sample amounted to 42 nurses at Dr. Drajat Prawiranegara Hospital who were selected through total sampling techniques. Bivariate analysis was carried out using chi-square test. The results showed that 54.8% of nurses had a poor level of knowledge, 76.2% had high motivation, 52.4% stated that hospital support was still lacking, and 69.0% of nurses had not fully implemented OHS. The results of the statistical test showed a significant relationship between knowledge (p=0.002), motivation (p=0.018), hospital support (p=0.014) and the implementation of OHS. Routine OHS-related training programs, the reward system to motivate nurses, and the commitment of hospital management in providing facilities and policies that support the implementation of OHS in a sustainable manner should be strengthened.